A model of turnover intent and turnover behavior among staff in juvenile corrections - Wells, James (Criminal justice and behavior, 2016)
This study extended prior research on staff turnover in adult corrections to juvenile corrections by analyzing direct and indirect interrelationships among personal, work environment, job attitude, and turnover variables. Data came from a mail survey of youth worker staff as well as from agency archives. Race, age, tenure, input into decisions, and job stress had significant direct effects on job satisfaction, while organizational commitment was directly affected by gender, stress, and satisfaction. Tenure, satisfaction, and commitment directly affected intent, while only race and age directly affected actual turnover. Satisfaction and commitment performed significant mediating functions. Results suggest that staff turnover intent can be reduced by promoting job satisfaction and organizational commitment and, further, that these attitudes can be improved by providing staff greater input into decisions and reducing job stress. Future research must specify conditions under which intent predicts behavior, as the two were not significantly related in this study.